KARAKTERISTIK GULA CAIR DARI SISA EKSTRAKSI PATI PADA VARIASI JENIS DAN KONSENTRASI ASAM - Efendi, Muhamad Erwin; Hartiati, Amna; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 3 (2019): September, 2019)
This study aims to determine the effect of type and concentration of acid on the characteristics and best treatment of liquid sugar from the hydrolysis process. This study used a factorial randomized block design with two factors, namely treatment of type and concentration of acid as the first factor used, namely: 3%, 4%, and 5%. Each treatment is grouped into 2 based on the time of implementation. The second factor consists of 3 types of acids, namely: HNO3, H2SO4, and HCl. Each treatment is grouped into 2 based on the time of implementation. The variables observed were total sugar, Dextrose Equivalent, total dissolved solids, and reducing sugars. The results showed that the type treatment and acid concentration had a significant effect (P <0.05). The results of hydrolysis of the remaining extract of the best taro starch, namely by using the type and 5% HNO3 concentration, namely with the characters namely total sugar (4.94), reducing sugar (4.74%), total dissolved solids (6.13% brix), and DE (96.65%). Keywords: acid hydrolysis, residual extraction of starch, taro, liquid sugar, acid.